Tourist accommodation of castles and palaces located within the Lower Silesian Voivodeship - Adamska, Agnieszka (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
Properly prepared accommodation base, apart from specific tourist values, world situation and advanced infrastructure, has a great impact on contemporary tourism development. The paper focuses on main features of Lower Silesian tourist accommodation establishments founded in entered into the heritage register castles and palaces. As observed, tourist base is subject to dynamic changes and stands out with susceptibility to various factors, hence new types of lodgings with specific characteristics appear. One of the tendencies is growing interest in historical landmarks overnight stays. Simultaneously, the voivodeship, as the only one in Poland, despite ongoing pandemic, recorded increase in the number of accommodation enterprises. Therefore, it seems that there is a great need for further research aimed at understanding the potential and trends in such complexes creation.